2006
DOI: 10.2111/05-202r1.1
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Variation in Remnant Grasses After a Grassland-to-Shrubland State Change: Implications for Restoration

Abstract: Around the world rangelands that have been degraded, such as historical desert grasslands now dominated by woody shrubs, are resistant to restoration efforts. The goal of this descriptive research was to examine the potential for black grama (Bouteloua eriopoda [Torr.] Torr.) recovery by remnant plants in a degraded area as a function of plant location across a landscape. Our objectives were 1) to document the historical dominant vegetation as a perennial grassland and determine broad-scale changes in dominanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 19 publications
1
8
0
1
Order By: Relevance
“…Hiers et al (2009) measured small-scale variations in surface fuel using LiDAR and found that fuelbed depths become spatially independent after small distances (0.5 m 2 ). Spatial variability of grasslands have been described in the context of population dynamics and restoration potential but have not been related to fuel characteristics (Peters et al 2006). Theobald (2013) found that while fine-scale variation in fuels dictated fire behavior, the distribution of CWD dictated germination in longleaf pine ecosystems.…”
Section: Landscape Ecologymentioning
confidence: 99%
“…Hiers et al (2009) measured small-scale variations in surface fuel using LiDAR and found that fuelbed depths become spatially independent after small distances (0.5 m 2 ). Spatial variability of grasslands have been described in the context of population dynamics and restoration potential but have not been related to fuel characteristics (Peters et al 2006). Theobald (2013) found that while fine-scale variation in fuels dictated fire behavior, the distribution of CWD dictated germination in longleaf pine ecosystems.…”
Section: Landscape Ecologymentioning
confidence: 99%
“…Hiers et al [21] measured small-scale variations in surface fuel using LiDAR and found that fuelbed depths become spatially independent after small distances (~0.5 m 2 ). Spatial variability of grasslands have been described in the context of population dynamics and restoration potential but have not been related to fuel characteristics [22]. Theobald [23] found that while fine scale variation in fuels dictated fire behavior, the distribution of CWD dictated germination in longleaf pine ecosystems.…”
Section: Introductionmentioning
confidence: 99%
“…Peters et al 2006) and increased plant diversity and soil function (Maestre et al 2009, Eldridge et al 2011. Increasing shrub density, however, also results in declining pastoral productivity (van Auken 2009).…”
Section: Introductionmentioning
confidence: 99%